Maraval Reservoir, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Davidson and Todd Ltd., Trinidad, 2010)
A drawing of several gentlemen looking at the full reservoir against the backdrop of two colonial houses almost surrounded by thick natural vegetation. Affixed to the undated postcard is a Trinidad one penny stamp. The addressee is Nettie Furrows of Springfield, Massachusetts, USA.
Colour: Black and White; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Maraval; Reservoirs--Trinidad and Tobago; 1907; Architecture--Trinidad and Tobago; Men--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Plants, Potted--Trinidad and Tobago